ปรัชญาของมูลนิธิศิลปะเพื่อมวลมนุษย์ - ณชนก หล่อสมบูรณ์ (วารสารศิลปกรรมศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ คณะศิลปกรรมศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2022)
This research is a qualitative research aiming to analyze the philosophy of "Arts for All" foundation, according to Edmund Burke Feldman s Philosophy of arts education in five dimensions: 1) the social dimension, 2) the economic dimension, 3) the political dimension, 4) the psychological dimension, and 5) the knowledge and morality dimension. The in-depth interviews and document studies were utilized as the main data collection methods. The study found that "Going beyond limits" philosophy was based on humanism that focused on the value of all human beings and the belief in human abilities. Therefore, it was encouraged to motivate human beings to have confidence in their potential and ability. This philosophy was consistent with existentialism that aimed to promote self-development, freedom, choice, and responsibility and Edmund Burke Feldman s Philosophy of art education in 5 dimensions.